Diferenciação química de quatro espécies de Bauhinia (pata-de-vaca) - Aquino, Amanda Jordano (2018)
The search for new compounds from natural products with high biological activity is an arduous task that has improved due to the evolution of instrumental analytical techniques. In addition, the use of medicinal herbs for the treatment of diseases is still used for generations and the pharmacological studies of these drugs evidences their biological activity. In spite of this, deforestation still grows in Brazil. The Bauhinia (pata-de-vaca), with more than 60 native species, are extensively used in Brazilian popular medicine for the control of diabetes. Thus, in 2009 B. forficata, B. variegata and/or B. affinis were included in the National List of Medicinal Plants of Interest to SUS (RENISUS). In this context, the present work reports the results of LC-HRMS and LC-SPE / NMR identification of compounds in leaves of Bauhinia longifolia, a species with few phytochemical studies, and the chemical differentiation of B. forficata, variegata, longifolia and affinis using LC-HRMS and unsupervised chemometric tools. Chromatographic conditions were developed using full factorial design and liquid chromatographic knowledge. With this method it was possible to characterize 74 (seventy-four) compounds in Bauhinia longifolia. Most of these were first identified in this species, namely phenolic acids, flavonoids O-glycosylated and proanthocyanidins. In addition, 6 (six) were isolated by LC-SPE and identified by NMR in which four (miricitrin, juglanin, afzelin, bauhiniastatin 2) are unknown for this species, especially bauhiniastatin 2 reported in the literature with anticancer properties. Futhermore, the chemical profile by LC-HRMS analyzed by hierarchical cluster analysis and principal component analysis differentiated the 4 species of Bauhinia and 24 other compounds were inferred. Thus, 99 (ninety-nine) compounds were identified in this thesis by providing important information that can be used in the quality control of ethanolic extracts of Bauhinia leaves, as well as to explain ethnotherapeutic properties, pharmacological and toxicological actions.